\(\displaystyle \displaystyle z^{2} + 3 \bar z = \frac{4}{z} \Longrightarrow^{*z} \, \, z^{3}+3|z|^{2}=4 \Longrightarrow \, z^{3}=4-3|z|^{2}\Longrightarrow \, z^{3}=4-3(x^{2}+y^{2})
\)
\(\displaystyle \displaystyle z^{3}=(x+iy)^{3}=x^{3}-3xy^{2}+ib(3x^{2}-y^{2}) \Longrightarrow \, x^{3}-3xy^{2}+ib(3x^{2}-y^{2})=4-3(x^{2}+y^{2}) \)
\(\displaystyle \displaystyle b(3x^{2}-y^{2})=0 \Longrightarrow \, 3x^{2}-y^{2}=0 \Longrightarrow \, y^{2}=3x^{2}\Longrightarrow^{y<0} y=\pm x \sqrt{3} \)
\(\displaystyle \displaystyle x^{3}-3xy^{2}=4-3(x^{2}+y^{2}) \Longrightarrow x^{3}-3(y^{2}(x-1)-x^{2})-4=0 \)